Suspected appendicitis during pregnancy: prevalence and management at prince Hashem Ben AL-Hussein Hospital (Zarqa/Jordan) - Al-Dahamsheh, Hasan (Journal of College of Medical Sciences-Nepal, 2012)
To evaluate the clinical picture and outcome of suspected appendicitis in pregnant women. Retrospective analytic study of 28 appendectomies performed during pregnancy for suspected appendicitis in our hospital at period April 2004 to September 2006. All files and medical records of these patients were analyzed and studied. Those including variables (demographic, clinical, laboratory and surgical outcomes data) were collected retrospectively. Prevalence of appendicitis was calculated from the total number of deliveries and abortions that occurred during this period. Numbers of correct and wrong diagnosis were reported and comparison of perinatal outcome, maternal morbidity and different variables in negative and positive laparotomies performed. The prevalence of suspected appendicitis in pregnancy is 0.29%. Incidences of negative laparotomies were 36%. The most diagnostic findings for acute appendicitis were history of periumbilical pain, anorexia and Rt iliac fossa findings. Half of wrong diagnosis were related to premature labor pain or abortion. The prevalence of suspected appendicitis during pregnancy in our environment during this period was higher than the reported incidence and rate of wrong diagnosis still high. Good clinical assessment with adjunct ultrasonic examination could reduce the incidence of negative laparotomies or prevent late complication. Delay in operation leading to higher rate of maternal morbidity and adversely affect the obstetric outcome. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-1, 36-43 DOI: http://dx.doi.org/10.3126/jcmsn.v8i1.6824